SEJARAH PELABUHAN CAMAT DI SELATPANJANG KABUPATEN KEPULAUAN MERANTI - MARA ANJANI; Kamaruddin Oemar; Tugiman ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: A port is a location on a coast or shore containing one or more dock ships and transfer people or cargo to or from land. Port locations are selected to optimize access to land and navigable water, for commercial demand, and for shelter from wind and waves. Indonesia as an archipelago countrywould make the port has a very strategic and vital role. Indonesia has many ports that exist since colonial ages and still remain operational, one of which is Camat Port. The purpose of this study is to know the history of the port in Selatpanjang that being one and only port since Dutch Colonial Ages until 1990s. the method was descriptive method, where data were collected through interviews, documentation and literature (library studies). Data analysis was done by qualitative. Time the study began after the publication of the research license until the completion of the last revision of the essay writer. The results showed that the Camat Port in Selatpanjang formerly named is Boom Selatpanjang which has a very long history. Based on these results, it can be concluded that the first built by the Dutch Colonial Government to facilitate Ducth Colonial access towards Selatpanjang.Key Words: Port, Camat, Selatpanjang.